The effect of simvastatin–Acalypha indica Linn. combination on the improvement of fatty pancreas in rats induced with a high fructose and cholesterol diet - Krisnamurti, Desak Gede Budi; Farida, Siti; Putri, Rizky Clarinta; Fachri, Wilzar; Purwaningsih, Erni Hernawati (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: The study aimed to determine the effect of Acalypha indica Linn. (AI) root extract and a combination of simvastatin–AI on improving the fatty pancreas in Sprague–Dawley rats induced with a high fructose and cholesterol diet. Materials and Methods: Twenty-four male Sprague–Dawley rats were induced with a high fructose and cholesterol diet for 4 weeks before being divided into four groups. Each group receiving treatments consisting of simvastatin only, A. indica extracts only, or simvastatin–A. indica extract combination. A histological examination was conducted to determine the effect of each treatment. Also, one-way analysis of variance (ANOVA) and post-hoc Bonferroni test were conducted to assess the comparison of groups from the histological examination. Results: Significant improvement was found in fatty pancreas between rats without therapy and rats treated with simvastatin therapy (p = 0.024, 95% CI: 0.038–0.696), and also between rats without treatment and rats treated with simvastatin–A. indica extract combination therapy (p = 0.000, 95% CI: 0.241–0.873) using one-way ANOVA and the post-hoc Bonferroni test. Conclusions: The results of the combination of simvastatin–A. indica Linn. root extracts treatment showed a synergistic effect on the improvement of fatty pancreas, but further research is needed to find potential adverse effects on the interaction of these two substrates to confirm the safe use of this treatment. J. Adv. Vet. Anim. Res., 9(2): 346–350, June 2022 http://doi.org/10.5455/javar.2022.i601